The Gender Pay Gap, and Multiple Forms of Discrimination Against Female Migrant Workers: Anti-Discrimination Legislation in Slovakia, and the Current EU Approach - Molnári, Daniel (Central European Academy Law Review, 2025)
The migration of workers is inextricably linked with today’s increasingly globalised environment. Ensuring their equal and non-discriminatory status should be a prerequisite for their participation in the labour market. This particularly concerns their pay equality. The principle of equal pay for men and women has been part of the EU legal framework since the beginning of the integration processes. However, despite decades of efforts, gender pay equality has still not been achieved. A particular challenge in the field of effective implementation and real enforcement of equal pay is the position of female migrant workers. They face multiple forms of discrimination, both as women and as migrants. Legislation at the European and national level should therefore take into account all the discriminatory factors they face. However, the sustainable achievement of pay equality requires joint, mutually coordinated, and targeted solutions.